GURU: IDEOLOGI DAN PROFESI - Samad, Duski (AT-TALIM, 2013)
Teaching profession is not a common job, it carries certain sets of ideology.Â  A teacher who is committed to certain ideology will likely to be more successful and highly appreciated in pursuing her career.Â  It has already been proved through the history that best teachers are born among individuals who possessed pedagogical ideology.Â  Great cares have been continuously given by the Government to improve teachersâ lives and positions through Law number 14 year 2005 dealing with teacher and lecturer.Â  The improvement of teacherâs status as professional staff has brought about wide impacts.Â  Its positive impact is that teacher position becomes more prestigious and it affects to the betterment of their welfares.Â  However, there is a critique to the procedures of certification that it doesnât provide significant impact to the quality improvement of education.CopyrightÂ Â©Â 2013 by Al-TalimÂ AllÂ rightÂ reservedDOI:Â 10.15548/jt.v20i2.32